Uso da serologia na avaliação da preferência alimentar de predadores pelas principais pragas da cultura do milho (Zea mays L.) - Redoan, Ana Carolina Maciel (2016)
This study objective to identify the diversity of predators through the use of serology producing specific antiserums for the main pests found in maize, Spodoptera frugiperda, Helicoverpa armigera and H. zea, Rhopalosiphum maidis and uses it to determine their predators. Pest samples were macerated in 0.85% saline solution. The macerated were centrifuged and the supernatants used as immunizing antigens for obtaining antiserum. For this purpose, a rabbit was immunized with 3.0 ml of the immunizing antigen on the lymph node region. Homologous serological tests were performed in double diffusion in agar. Homologous serological reactions were positive after seven days of antigen inoculation. The technique has sensitivity to detect predation of the four pests studied in this paper. The tests were positive for a prey in the digestive tract of the predator to 96 hours of ingestion. Regarding the number of preys, there was no difference in the lines, they only grew stronger and sharper. In laboratory, D. luteipes, O. vnigrum and C. externa presented preference for R. maidis and E. annulipes for S. frugiperda. In tests where predators were collected in the field, serological tests showed that there was a certain food preference of D. luteipes and O. v-nigrum by S. frugiperda. E. annulipes, H. axyridis, E. connexa and C. externa, by the aphid. After a single injection of antigen in rabbit’s lymph node region, it was possible to get an antiserum specific for pests of corn.